2016
DOI: 10.2147/ndt.s111230
|View full text |Cite
|
Sign up to set email alerts
|

Two-year prognosis after residential treatment for patients with alcohol dependence: three chief guidelines for sobriety in Japan

Abstract: BackgroundIn Japan, the three chief traditional guidelines for sobriety (3CGS) are regular medical checkups, participation in self-help groups, and pharmacotherapy with antidipsotropics. However, the official record of the origins of 3CGS is not clear. The aim of this current study was to assess 3CGS by an examination of the prognosis of patients with alcohol dependence 2 years after their discharge from a residential treatment program.Subjects and methodsThe association between subjects’ abstinence from alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Most alcoholic patients are treated during outpatient services such as the intensive outpatient program. [15][16][17][18] Therefore, the present findings suggest the importance of outpatient services with a multidisciplinary approach for alcoholic patients. Further prospective studies with a large sample size are needed to assess this significance.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Most alcoholic patients are treated during outpatient services such as the intensive outpatient program. [15][16][17][18] Therefore, the present findings suggest the importance of outpatient services with a multidisciplinary approach for alcoholic patients. Further prospective studies with a large sample size are needed to assess this significance.…”
Section: Discussionmentioning
confidence: 55%
“…Regarding the outpatient multidisciplinary program, this study showed that alcoholic individuals using only the outpatient alcoholic treatment program could continue to visit the hospital more than those without any multidisciplinary program, but there were no differences in alcohol abstinence among the two groups. Most alcoholic patients are treated during outpatient services such as the intensive outpatient program 15–18 . Therefore, the present findings suggest the importance of outpatient services with a multidisciplinary approach for alcoholic patients.…”
Section: Discussionmentioning
confidence: 65%
“…The guidelines (3CGS) imply regular medical checkups, participation in self-help groups, pharmacotherapy with antidipsotropics for patients with alcohol problems. The abstinence rates for patients who followed the guidelines were significantly higher in comparison with patients who did not follow the guidelines (20).…”
Section: Methodsmentioning
confidence: 83%